Selection of Organophsophate Resistant Drosophila Melanogaster over Twelve Generations - Prevec, John Sheldon (My University, 1989)
Twenty-five different iso-chromosomal III lines of Drosophila melanogaster, with known haplotypes, were mixed and selected on malaoxon over twelve generations in order to find the importance of variants already present in the Drosophila genome relative to new mutations in the evolution of insecticide resistance. Measurements of mixed function oxidase and acetylcholinesterase activities, as well as insecticide resistance, were made over the twelve generations of selection and on the the iso-chromasomal III lines extracted after the selection was completed. These measurements were compared to those made of the twenty-five lines before selection. This comparison indicated that 52A, one of the origional twenty-five lines, may have been selected during this experiment. Comparisons of a possible cytochrome P-450 produced by a previously selected line of Drosophila called D23, and the DNA which is probably responsible for the production of this P-450, with the microsomal proteins and total genomic DNA of the selected lines were made using the techniques of Western and Southern blotting. The results of these procedures suggested that the mechanism of resistance used by the selected lines was not the same mechanism of resistance used by the D23 line.
Keywords: iso-chromosomal, Drosophila melanogaster, haplotypes, malaxon, insectiside